Jaundice due to hydatid compression of the bile ducts - Praderi, Raúl; Gómez Fossati, Carlos; Praderi, Luis (Cirugía del Uruguay, 1973)
Compression of main biliary tract by non-ruptured hydatid cysts, may cause obstructive jaundice with characteristics similar to those caused by biliary or pancreatic cancers. This rare cases may occur in cysts of the quadrate or Spigelian lobe which displace the. hepatic duct in the portal fissure, as well as in sone retropodicular or interportocoledochal cysts which occlude or laminate the coledochus. The latter may be accompanied by compressión or thrombosis of the vena porta, as was the case in two of the five patients. Treatment consisted of drainage of cysts and main biliary tract, except in cases when the latter's calibre was small, as was the case in one of the patisnts on whom colecystostomy was performed. Evolution of three of the patients was good, but those with portal thrombosis died.